Cytoplasmic tails of beta 1, beta 2, and beta 7 integrins differentially regulate LFA-1 function in K562 cells. - Lub, M (1997)
The beta 2 integrin lymphocyte function-associated antigen 1 (LFA-1) mediates activation-dependent adhesion of lymphocytes. To investigate whether lymphocyte-specific elements are essential for LFA-1 function, we expressed LFA-1 in the erythroleukemic cell line K562, which expresses only the integrin very late antigen 5. We observed that LFA-1-expressing K562 cannot bind to intercellular adhesion molecule 1-coated surfaces when stimulated by phorbol 12-myristate 13-acetate (PMA), whereas the LFA-1-activating antibody KIM185 markedly enhanced adhesion. Because the endogenously expressed beta 1 integrin very late antigen 5 is readily activated by PMA, we investigated the role of the cytoplasmic domain of distinct beta subunits in regulating LFA-1 function. Transfection of chimeric LFA-1 receptors in K562 cells reveals that replacement of the beta 2 cytoplasmic tail with the beta 1 but not the beta 7 cytoplasmic tail completely restores PMA responsiveness of LFA-1, whereas a beta 2 cytoplasmic deletion mutant of LFA-1 is constitutively active. Both deletion of the beta 2 cytoplasmic tail or replacement by the beta 1 cytoplasmic tail alters the localization of LFA-1 into clusters, thereby regulating LFA-1 activation and LFA-1-mediated adhesion to intercellular adhesion molecule 1. These data demonstrate that distinct signaling routes activate beta 1 and beta 2 integrins through the beta-chain and hint at the involvement of lymphocyte-specific signal transduction elements in beta 2 and beta 7 integrin activation that are absent in the nonlymphocytic cell line K562.